(untitled) (Iranian Journal of Kidney Diseases, 2021)
Coronavirus disease (COVID-19), declared as a pandemic has affected millions of people and caused unprecedented number of death. The disease is caused by a severe acute respiratory syndrome related coronaviruses-2 virus which enters cells by binding with the host angiotensin converting enzyme-2 and CD147 protein. Among COVID-19 patients admitted to a hospital, hypertension, diabetes and obesity are the most common co-morbidities. A majority of COVID-19 hospitalized patients are found to have proteinuria and hematuria which is associated with higher risk of in-hospital mortality. Studies have reported high incidence of acute kidney injury (AKI) among COVID-19 patients admitted to hospital (10 to 43%) and intensive care unit (43-75%). These patients with AKI have much higher need for mechanical ventilation, vasopressor use and critical care. In addition, proportion of patients with AKI who require renal replacement (RRT) therapy is greatly increased. Acute tubular injury, cytokine storm induced systemic inflammatory response, endothelial injury and dysfunction are the main mechanisms of AKI. In addition, direct viral invasion of tubules, lymphocytic infiltration and complement mediated (C5b- 9) related injury is also seen. Mortality risk among patients with AKI and those in need of RRT is greatly amplified. Appropriate timing and choice of RRT for these patients is not well defined but will need to take in account the clinical condition, anticipation of their clinical course and availability of dialysis resources. Risk of AKI and death is also increased among kidney recipients and patients with chronic kidney disease.